Genetically increased circulating FUT3 level leads to reduced risk of idiopathic pulmonary fibrosis: a Mendelian randomisation study - Nakanishi, Tomoko; Cerani, Agustin; Forgetta, Vincenzo; Zhou, Sirui; Allen, Richard J.; Leavy, Olivia C.; Koido, Masaru; Assayag, Deborah; Jenkins, R. Gisli; Wain, Louise V.; Yang, Ivana V.; Lathrop, G. Mark; et al. (The European respiratory journal, 2022)
Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal fibrotic interstitial lung disease. Few circulating biomarkers have been identified to have causal effects on IPF. To identify candidate IPF-influencing circulating proteins, we undertook an efficient screen of circulating proteins by applying a two-sample Mendelian randomisation (MR) approach with existing publicly available data. For instruments, we used genetic determinants of circulating proteins which reside to the encoded gene ( -single nucleotide polymorphisms (SNPs)), identified by two genome-wide association studies (GWASs) in European individuals (3301 and 3200 subjects). We then applied MR methods to test if the levels of these circulating proteins influenced IPF susceptibility in the largest IPF GWAS (2668 cases and 8591 controls). We validated the MR results using colocalisation analyses to ensure that both the circulating proteins and IPF shared a common genetic signal. MR analyses of 834 proteins found that a 1 sd increase in circulating galactoside 3(4)-l-fucosyltransferase (FUT3) and α-(1,3)-fucosyltransferase 5 (FUT5) was associated with a reduced risk of IPF (OR 0.81, 95% CI 0.74-0.88; p=6.3×10 and OR 0.76, 95% CI 0.68-0.86; p=1.1×10 , respectively). Sensitivity analyses including multiple -SNPs provided similar estimates both for FUT3 (inverse variance weighted (IVW) OR 0.84, 95% CI 0.78-0.91; p=9.8×10 and MR-Egger OR 0.69, 95% CI 0.50-0.97; p=0.03) and FUT5 (IVW OR 0.84, 95% CI 0.77-0.92; p=1.4×10 and MR-Egger OR 0.59, 95% CI 0.38-0.90; p=0.01). FUT3 and FUT5 signals colocalised with IPF signals, with posterior probabilities of a shared genetic signal of 99.9% and 97.7%, respectively. Further transcriptomic investigations supported the protective effects of for IPF. An efficient MR scan of 834 circulating proteins provided evidence that genetically increased circulating FUT3 level is associated with reduced risk of IPF.